Nestmate larval discrimination by workers in the swarm-founding wasp Polybia paulista. Issue 2 (4th March 2017) - Kudô, Kazuyuki; Oliveira, Lucas A.; Mateus, Sidnei; Zucchi, Ronaldo; Nascimento, Fabio S.
Abstract : The discrimination of nestmates is an important requisite to avoid exploitation by unrelated individuals. Although recognition among adult social wasps has been examined in detail, few studies have investigated brood discrimination by adults. Adult females of some Polistes species were previously shown to discriminate their nestmate larvae on the basis of cuticular hydrocarbons. However, nestmate larval discrimination has not been studied in polygynous swarm-founding wasps of the tribe Epiponini. Whether the workers of Polybia paulista recognised their own larvae when presented outside the nest comb was investigated in the present study. We also compared the cuticular chemical profiles of 5th instar larvae from different colonies. Workers did not bite non-nestmate larvae more frequently than their nestmate larvae. However, they spent significantly more time licking with their nestmate larvae than with non-nestmate larvae. These behavioural tests suggest that the workers of P. paulista may have the ability to distinguish between larvae from their own colony and alien larvae. The epicuticle of larvae had 69 compounds consisting of linear and methyl branched compounds with chains from 19 to 36 carbon atoms. Analyses of the cuticular extracts of 5th instar larvae from the experimental colonies significantly allocated (100%) in their predicted groups, suggesting that discrimination of own larvae by the workers may be mediated by colony-specific, larval-borne cues. These results suggest that workers of the swarm-founding wasp P. paulista recognised the larvae of their own nest from alien larvae according to distinct cuticular chemical profiles. Because it is not so far known that swarm-founding wasps exhibit intraspecific colony usurpation, this discrimination is not used in their colonial life even if workers recognise the chemical cues between more or less related larvae. Our results also imply that nestmate larval recognition could be evolved in colonies with many matrilines, as P. paulista colonies have.